Face identification: the effects of head orientation and disguise on initial eye movements - Muhammad Shahir Adha Modh Zakaria (Nanyang Technological University, 2022)
Eye movement studies in face perception have given us an insight to how the brain processes facial information, but most of these studies have looked at faces presented in frontal view, rarely considering the occlusion of face features brought about by differences in head orientation or deliberate disguise that we navigate on a daily basis. Humans optimally land their initial fixations towards the nose bridge, just below the eyes when identifying full front-faces (Peterson & Eckstein, 2012) but it remains to be explored the positions of initial fixations to faces rotated in depth where face features are shifted in relative position, changed in appearance or completely occluded. In Study 1, I investigated the effect of head orientation on initial fixation strategies. Eye movements of 32 observers to faces across 13 head orientations were recorded during a face identification task. Notably, the horizontal position of the initial fixation, normalized by the horizontal distance between the near eye and the nose bridge, formed a near quadratic relationship with head orientation. In Study 2, I looked at the effects of different forms of disguises on fixation strategies. Using a similar identification task as Study 1, I recorded 16 observers’ eye movements to faces covered with face mask and/or sunglasses. Both studies demonstrated a clear preference to fixate close to the eyes but initial fixations to faces rotated in depth were systematically displaced horizontally from the eye region. In the complete absence of eye information, observers still preferred to land their initial fixations around the eyes, although with greater variability in the distribution of fixations. My findings provide evidence for viewpoint-dependency and the persistence of our preference to initially fixate relatively close to the eyes even when completely occluded from view.